AL-KHAUF DAN AL-RAJAâ MENURUT AL-GHAZALI - Dacholfany, M. Ihsan (LP3M STAI DARUSSALAM LAMPUNG, 2014)
The study form Al-Ghazali abouty Al-Khauf basically urges the people toremember many more about Allah SWT. This also urges to do His order andcasts away His prohibitation. But, all of it will not be perfect if it is not runtogether with the knowledge. It is he explicits that Al-Khauf is a favor ofknowledge. With the knowledge, people will consider Allah SWT and loveHim and so to the King. It is the hope that is one thing better than feelingscarry. It is because the servants which are closer to Allah SWT, are theservants He loves.Keywords: Al- Ghazali, Al-Khauf, Al Rajaâ